2009
DOI: 10.1016/j.pbb.2008.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Novelty-induced locomotion is positively associated with cocaine ingestion in adolescent rats; anxiety is correlated in adults

Abstract: The present studies assessed the roles of sex, age, novelty-seeking and plus-maze behavior on cocaine drinking in rats. Cocaine/saccharin solution was available in three daily, 5-hour sessions then a saccharin-only solution was also available in following sessions. In the one-bottle drinking phase, early and late adolescent males, post-natal day 28 (PN28) and PN42, consumed more cocaine/ saccharin solution than young adults (PN65), but females did not exhibit significant age differences. Adolescents of both se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 95 publications
3
27
0
Order By: Relevance
“…The close relationship between trait-like anxiety and increased propensity to escalate cocaine SA may seem difficult to reconcile with reports that cocaine promotes anxietylike behavior in both human users (Anthony et al 1989;Bystritsky et al 1991) and in animals Ettenberg et al 1999;Blanchard et al , 2000. However, it has previously been shown that rats displaying high anxiety on the EPM have an increased tendency to drink an oral solution of cocaine (Walker et al 2009), an enhanced motivation for the drug under a progressive-ratio schedule of reinforcement (Homberg et al 2002; but see, Bush and Vaccarino (2007)), and acquire a cocaine conditioned place preference whereas LA rats do not (Pelloux et al 2009). One explanation may be that the anxiogenic effects of a b c d Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The close relationship between trait-like anxiety and increased propensity to escalate cocaine SA may seem difficult to reconcile with reports that cocaine promotes anxietylike behavior in both human users (Anthony et al 1989;Bystritsky et al 1991) and in animals Ettenberg et al 1999;Blanchard et al , 2000. However, it has previously been shown that rats displaying high anxiety on the EPM have an increased tendency to drink an oral solution of cocaine (Walker et al 2009), an enhanced motivation for the drug under a progressive-ratio schedule of reinforcement (Homberg et al 2002; but see, Bush and Vaccarino (2007)), and acquire a cocaine conditioned place preference whereas LA rats do not (Pelloux et al 2009). One explanation may be that the anxiogenic effects of a b c d Fig.…”
Section: Discussionmentioning
confidence: 93%
“…In preclinical studies, high anxiety as measured in the elevated plus maze (EPM) (Pellow et al 1985) predicts increased propensity to develop conditioned place preference for cocaine (Pelloux et al 2009), as well as higher oral intake levels (Walker et al 2009), and increased motivation to self-administer cocaine (Homberg et al 2002). Additionally, exposure to, or withdrawal from, cocaine and heroin increases anxiety (Rogerio and Takahashi 1992;Schulteis et al 1998;Zhou et al 2003;Le Merrer et al 2006;Ambrose-Lanci et al 2010;Salas-Ramirez et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that adult but not prepubertal female rats ingest more cocaine and two laboratories have reported the appearance of faster acquisition of cocaine self administration during adolescence (Perry et al 2007; Carroll et al 2008; Lynch 2008; Walker et al 2009). While both adolescent male and female rats acquire nicotine self administration faster than adults, levels of self-administration actually fall in males as they enter adulthood, while females maintain levels of intake (Levin et al 2003; Levin et al 2007).…”
Section: Part 3: Sex Gonadal Steroids and Addiction In Adolescencementioning
confidence: 86%
“…Since the initial report by Piazza et al (1989), several studies have confirmed that HR rats show increased amphetamine-induced activity (Bevins et al, 1997) and amphetamine self-administration (Piazza et al, 1990(Piazza et al, , 2000Pierre and Vezina, 1997;Klebaur et al, 2001a;Cain et al, 2005Cain et al, , 2006Cain et al, , 2008 compared with LR rats. The differences between HR and LR rats in amphetamine self-administration are similar for both males and females (Klebaur et al, 2001a), and these individual differences generalize to other stimulant drugs, including cocaine (Mantsch et al, 2001;Sell et al, 2005;Kabbaj, 2006;Belin et al, 2008Belin et al, , 2011Walker et al, 2009) and methamphetamine (Bevins and Peterson, 2004;Gancarz et al, 2011). Nicotine self-administration also is greater in HR rats than in LR rats (Suto et al, 2001), although these individual differences may not occur in nicotine-induced hyperactivity .…”
Section: Preclinical Behavioral Neuropharmacologymentioning
confidence: 92%